2020
DOI: 10.21325/jotags.2020.554
|View full text |Cite
|
Sign up to set email alerts
|

The Problems Faced by Hotel Security Managers: Antalya Case

Abstract: Trust and security are the common problems for everybody. In this respect, we can imply that the tourists in the accommodation facilities pay more attention to this, which makes the security departments in these facilities more and more important. Accordingly, this study was conducted in order to reveal the problems faced by the managers of the security departments struggling for the tourist to have a peaceful and comfortable holiday while staying in the accommodation facilities. The study was completed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Aspects of safety and security services are covered in the literature that is now available on hotel safety and security. Recent research has examined the challenges faced by hotel managers in maintaining security (Efendi, 2020), creating a secure hotel experience for female guests (H. J. Wang & Wu, 2020), the impact of security issues on guest loyalty in hotels (Nwokorie & Igbojekwe, 2019), the compliance of information security policies (X. Wang & Xu, 2021), the evaluation of hotel building fire protection (Prastowo & Indriastuti, 2023), and hotel managers' opinions on the significance of safety and security measures (Anuar et al, 2019).…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…Aspects of safety and security services are covered in the literature that is now available on hotel safety and security. Recent research has examined the challenges faced by hotel managers in maintaining security (Efendi, 2020), creating a secure hotel experience for female guests (H. J. Wang & Wu, 2020), the impact of security issues on guest loyalty in hotels (Nwokorie & Igbojekwe, 2019), the compliance of information security policies (X. Wang & Xu, 2021), the evaluation of hotel building fire protection (Prastowo & Indriastuti, 2023), and hotel managers' opinions on the significance of safety and security measures (Anuar et al, 2019).…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…The main challenge that influences the development of the B&B industry negatively, also includes adverse government policies, and the general absence of guides or policy development on accommodation security, which is very important and should not be under-played for the benefit of the accommodation industry [10]. B&B's create employment, and they are registered businesses, paying tax (income and Vat) to the government to some form of protection, and it would appear that the government is "failing them by taking much time in providing important services required for successful business operations" [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twenty of the participants were black, which is not surprising as the research area is predominantly black. Efforts were made by the author to ensure that the gender and communication abilities were considered for the research participants to be able to express their opinions freely [3].…”
Section: Ethnic Group Of Participantsmentioning
confidence: 99%
“…Efendi [51] indicated that a hotel's security systems must be managed by the personnel in charge. Video systems, either visible or hidden, provide a sense of safety to customers and employees, and they are a priority for hotel managers [52,53].…”
Section: Dimensions Of Safety and Security In Hotelsmentioning
confidence: 99%
“…The alarm systems installed inside and outside the hotel; in car parks; and in conference halls, offices, and rooms detect unauthorized access, locate the intruders, and alert both employees and authorities, thus protecting the hotel's customers, assets, and facilities [54]. Efendi [51] argued about the different types of internal and external sensors which detect movement and vibrations and which include technical systems [55] capable of sending signals to the hotel's employees and of alerting about any suspicious activity.…”
Section: Dimensions Of Safety and Security In Hotelsmentioning
confidence: 99%